Propuesta de un modelo de control interno para el manejo de la información contable de las cuentas por cobrar a clientes y tesorería, empleando la metodología coso I, para la empresa Harkon S.A.S. de la ciudad Santiago de Cali - Valle del Cauca. (2020)
The purpose of this research is to propose an internal control model for the company Harkon SAS, dedicated to the activities of architecture and Civil engineering, the study focused on accounts receivable from clients and treasury to improve processes, optimize resources, analyze and study the risks that have arisen in the development of activities. Two descriptive and qualitative research methods were used, where information was collected, activities were described to analyze failures and risks and thus propose control actions. In the end, conclusions and recommendations are reached for the company, highlighting the importance of implementing the tool and communicating the findings found in this research to all levels of the organization. Highlighting the support in the COSO I model, which provides key elements for the continuous improvement of the company